Evolution of life history and behavior in Hominidae: Towards phylogenetic reconstruction of the chimpanzeehuman last common ancestor - Duda, Pavel (Jihočeská univerzita, 2017)
The origin of the fundamental behavioral differences between humans and our closest living relatives is one of the central issues of evolutionary anthropology. In this study we performed a series of phylogenetic comparative analyses using 65 selected life-history and behavioral characters for all extant hominid species to reconstruct the ancestral character states of the last common ancestors of Hominidae, Homininae and Hominini (the chimpanzee-human last common ancestor). These analyses show that many fundamental behavioral and life-history attributes of hominids (including humans) are evidently ancient and likely inherited from the common ancestor of all hominids. On the other hand, numerous behaviors present in extant great apes represent their own terminal autapomorphies (both uniquely derived and homoplastic). We demonstrate that phylogenetic reconstruction of ancestral states is able to provide a detailed suite of behavioral, ecological and life-history characters for each hypothetical ancestor. The living great apes therefore play an important role for the identification of the traits found in the chimpanzee-human last common ancestor, some of which are likely to represent behaviors of the fossil hominins.
Evolution of life history and behavior in Hominidae: Towards phylogenetic reconstruction of the chimpanzeehuman last common ancestor